The furnace for crystal growth by directional solidification in skull crucible - Таранюк, Владимир Иванович; Гектин, Александр Вульфович; Колесников, Александр Владимирович (Eastern-European Journal of Enterprise Technologies, 2014)
The furnace, based on the skull method for obtaining laboratory samples of halide crystals (40 mmin diameter and15 mmhigh) with the melting temperature of900 °C, is considered in the paper. This technological solution allows growing crystals without using expensive platinum crucibles and moving or rotating design elements. The process control system and the thermal unit design are designed for determining and controlling temperature and a thermal gradient for carrying out crystal growth and minimizing the skull layer thickness, preventing the contact of melt with crucible and obviating crystal contamination. Placed in a vacuum vessel and sealed independently, the crucible allows controlling the impurity composition of the output crystal. The grown PbF2 and LiF polycrystals demonstrate the effectiveness of the suggested approach in obtaining small crystals. The prospect of using this approach lies in the possibility of a transition from receiving laboratory samples of crystals to the industrial crystals.